A low cost and portable microwave imaging system for breast tumor detection - Izzat, Zainal Abidin. (Universiti Malaysia Sarawak (UNIMAS), 2017)
Microwaves are non-ionizing but it uses permitting frequent examinations. Plus, microwave electronics and test instrumentation had matured, compact, and relatively cheap compared to X-ray or MRI equipment. Breast cancer continues to be an unsolved health and societal problem. Breast cancer has a very high rate of incidence. Early detection is important as if malignant growth is removed before it reaches a size of about 1.5 cm in any given direction have the chances of survival are better than 90%. This project discusses the Microwave Imaging system using Arduino Mega that can be brought to rural areas. This project is also as communities’ services to help rural areas population that have difficulty to go for early breast screening. The focus of this project is on detection hardware as existing microwave imaging system is not portable to bring to rural areas. This project uses Arduino Mega 2560, NRF24L01 module and microstrip patch antenna. The Arduino Mega acts as microcontroller in this project and NRF24L01 module act as transmitter and receiver. Arduino board uses C language for programing and its board serves as user instruct. Arduino IDE is used for uploading the program code into the Arduino board. The system will measure the signal loss of receiver. The signal loss data will be gathered and will be integrated with breast cancer imaging algorithms.